Functional profile of oral plaque microbiome: Further insight into the bidirectional relationship between type 2 diabetes and periodontitis - Favale, Nicoletta; Farina, Roberto; Carrieri, Alberto; Simonelli, Anna; Severi, Mattia; Sabbioni, Silvia; Trombelli, Leonardo; Scapoli, Chiara (Molecular oral microbiology, 2024)
Increasing evidence support the association between the oral microbiome and human systemic diseases. This association may be attributed to the ability of many oral microbes to influence the inflammatory microenvironment. Herein, we focused our attention on the bidirectional relationship between periodontitis and type 2 diabetes using high‐resolution whole metagenomic shotgun analysis to explore the composition and functional profile of the subgingival microbiome in diabetics and non‐diabetics subjects with different periodontal conditions. In the present study, the abundance of metabolic pathways encoded by oral microbes was reconstructed from the metagenome, and we identified a set of dysregulated metabolic pathways significantly enriched in the periodontitis and/or diabetic patients. These pathways were mainly involved in branched and aromatic amino acids metabolism, fatty acid biosynthesis and adipocytokine signaling pathways, ferroptosis and iron homeostasis, nucleotide metabolism, and finally in the peptidoglycan and lipopolysaccharides synthesis. Overall, the results of the present study provide evidence in favor of the hypothesis that during the primary inflammatory challenge, regardless of whether it is induced by periodontitis or diabetes, endotoxemia and/or the release of inflammatory cytokines cause a change in precursor and/or in circulating innate immune cells. Dysbiosis and inflammation, also via oral–gut microbiome axis or adipose tissue, reduce the efficacy of the host immune response, while fueling inflammation and can induce that metabolic/epigenetic reprogramming of chromatin accessibility of genes related to the immune response. Moreover, the presence of an enhanced ferroptosis and an imbalance in purine/pyrimidine metabolism provides new insights into the role of ferroptotic death in this comorbidity.